Justified city primeval - Andron, Dave; Dinner, Michael 1953-; Olyphant, Timothy 1968-; Ellis, Aunjanue 1969-; Curtis-Hall, Vondie 1956-; Clemens, Adelaide 1989- (Sony Pictures Home Entertainment Inc., 2023)
Having left the hollers of Kentucky 15 years ago, Raylan Givens now lives in Miami, a walking anachronism balancing his life as a U.S. Marshal and part-time father of a 15-year-old girl. His hair is grayer, his hat is dirtier, and the road in front of him is suddenly a lot shorter than the road behind. A chance encounter on a desolate Florida highway sends him to Detroit. There he crosses paths with Clement Mansell, aka The Oklahoma Wildman, a violent, sociopathic desperado who's already slipped through the fingers of Detroit's finest once and aims to do so again. Mansell's attorney, formidable Motor City native Carolyn Wilder, has every intention of representing her client, even as she finds herself caught between cop and criminal, with her own game afoot as well. These three characters set out on a collision course in classic Elmore Leonard fashion, to see who makes it out of the City Primeval alive
Based on "City Primeval" and "Fire in the Hole" by Elmore Leonard
Picture: 2.00:1 Anamorphic Widescreen
Miniserie; USA, 2023
Keywords: Television series; Crime films; Melodramas; Melodrama; Kriminalserie; Fernsehserie; United States marshals / Drama; Fathers and daughters / Drama; Psychopaths / Drama; Crime / Drama; Detroit (Mich.) / Drama; Legal drama; Théâtre judiciaire; Fathers and daughters; Psychopaths; Michigan / Detroit; DVDs; Drama; Fiction television programs; Television crime shows; Video recordings for the hearing impaired; Action and adventure television programs; Legal television programs; Television programs; Émissions télévisées; Vidéos pour personnes handicapées auditives; Fictions télévisées; Fictions criminelles télévisées; Émissions d'aventures télévisées; Séries télévisées; Film; DVD-Video